Design and Implementation of a Wearable Sensor Node for Monitoring Mechanocardiographic Phenomena - Panula, Tuukka (My University, 2019)
Cardiovascular diseases are the most common cause of death in the world, fortunately most of which could be prevented. As the population ages, these conditions get even more frequent leading to millions of deaths every year. Atrial fibrillation (AF) is the most common arrhythmia (irregular heartbeat) affecting nearly 9 million people in the European Union only. Ischemic stroke is the most feared condition caused by AF with a five-fold risk of occurrence among AF patients. Commonly asymptomatic nature of AF causes many people to be left untreated. Mechanocardiography, including seismo-, ballisto- and gyrocardiography is the study of mechanical motion caused by cardiac activity. The quality of electromechanical sensors (accelerometers and gyroscopes) has improved greatly over the last decade due to MEMS (Microelectromechanical System) technology. The suitability of mechanocardiography for detecting AF has been assessed with promising results. In this thesis, a wearable sensor node for measuring the heart utilizing mechanocardiography is proposed. The device consists of a Bluetooth enabled MCU (Microcontroller unit), an IMU (Inertial Measurement Unit) and a 64-Mbit flash memory. The workflow of the design and implementation is documented in a reproducible manner. Verification is done by conducting both power consumption and mechanocardiographic measurements. Real time signal processing to detect AF is implemented as a proof-of-concept work to study the possibility for an independent AF detection device. As described in the thesis, the design was successfully implemented and provided high quality mechanocardiographic data. Minor improvements are proposed and possibility of a follow-up study is discussed along with potential for commercialization. A conference article based on this thesis was published in IEEE International Conference on Electronics Circuits and Systems (ICECS) in December 2018.